Endoleak Detection after Endovascular Aortic Aneurysm Repair Using Ultrasound Based on Nanoscale Bubble Contrast Agents and Their Effects on Vascular Smooth Muscle Cell Proliferation and Migration. (11th May 2021) - Pei, Siying; Feng, Yao; Fang, Shuqing; Jin, Song; Fan, Dongxu; Song, Fanxu; Wang, Hanrui
Abstract : Abdominal aortic aneurysm (AAA) is the most common vascular disease that causes disability and death. Its morbidity is relatively subtle, and the mortality rate is high. Clinically, endovascular aortic aneurysm repair (EVAR) has gradually become the primary treatment of AAA due to its unique advantages such as low trauma and low incidence of short-term complications. However, the outcome of EVAR is greatly compromised by the possible occurrence of endoleaks. Contrast-enhanced ultrasound (CEUS) is a promising alternative technique to detect endoleaks following EVAR due to lack of exposure to ionizing radiation. Traditional ultrasound contrast agents with an overlarge size (microscale) leading to reluctant accumulation in target organs and instability trigger the requirement of nanoscale contrast agents that enter tumor tissues through the enhanced permeability and retention effect. In this study, we used ultrasound based on nanoscale bubble contrast agents to evaluate endoleak detection after endovascular aortic aneurysm repair and analyzed the effects of nanoscale bubble contrast agents on vascular smooth muscle cell (VSMC) proliferation and migration. Among 52 AAA patients a month following EVAR, there were 16 cases of endoleaks after EVAR detected by nanobubble contrast-enhanced ultrasound, including 6 cases of type I endoleak (1 case of type Ia endoleak and 5 cases of type Ib endoleak), 7 cases of type II endoleak, and 3 cases of type III endoleak; there were 12 cases of endoleak after EVAR detected by computed tomography angiography (CTA), including 6 cases of type I endoleak (1 case of type Ia and 5 cases of type Ib), 5 cases of type II endoleak, and 1 case of type III endoleak. Six months after EVAR, 3 cases of type III endoleak were detected by both nanobubble contrast-enhanced ultrasound and CTA. Vascular smooth muscle cells (VSMCs) used for in vitro experiments were subjected to ultrasound irradiation and platelet-derived growth factor (PDGF) treatment with or without the addition of nanobubble contrast agents. After high-intensity and long-term irradiation (0.75 W/cm 2 and 1 W/cm 2 irradiation for 120 s and 150 s, respectively) by ultrasound with or without the addition of nanobubble contrast agents, PDGF-induced VSMC migration was inhibited (P < 0.01 ). Low-intensity and short-term ultrasound irradiation did not differ PDGF-induced VSMC migration (P > 0.05 ), but 0.5 W/cm 2 and 90 s ultrasound irradiation could significantly inhibit PDGF-induced VSMC migration without the addition of nanobubble contrast agents (P < 0.05 ). When VSMCs were irradiated at 1, 0.75, 0.5, and 0.35 W/cm 2 for 30 s to 150 s, ultrasound irradiation with or without the addition of nanobubble contrast agents remarkably reduced PDGF-induced VSMC proliferation, as evidenced by reduced OD values (P < 0.05 ). In conclusion, ultrasound based on nanoscale bubble contrast agents is an effective alternative detection method for the occurrence of AAA patients who are not suitable for CTA.